EVALUASI PERFORMA SIMPANG BERSINYAL DI PERSIMPANGAN KISARAN MEULABOH ACEH BARAT - Refiyanni, Meidia; Chaira, Chaira; Opirina, Lissa; Manik, Herza Arifin; Arafah, Yunita (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Meulaboh City as the center of the district capital in West Aceh certainly cannot be separated from problems in the field of transportation, especially at the crossroads. Increased population mobilization is a support for the community in carrying out various activities, to improve the economy. Meulaboh is one of the CBD (Central Business District) areas in West Aceh district, this causes the need for a signaling intersection evaluation. The problems considered in this study are what factors affect the performance of range intersections, what are alternative solutions to improve range intersection performance. The purpose of this study is to determine the factors that affect the performance of the Range intersection, and devise alternatives or solutions to improve the performance of the Range intersection in accordance with the physical conditions and needs of the local community, the method used in this study is MKJI 1997. Based on the results of the calculation analysis, the traffic flow volume of Manekroo road is 3856 junior high school / hour with a capacity of 1843.87 junior high school / hour, Imam Bonjol street 4229 junior high school / hour with a capacity of 1167.35, Gajah Mada street 6221 junior high school / hour with a capacity of 5638.91 junior high school / hour, Sisingamangaraja street 4157 junior high school / hour with a capacity of 3248.08 junior high school / hour. Based on the calculation of the cycle time adjusted for -3 seconds, this means that the intersection has entered saturation, which is marked by a high average intersection delay value of 891.58 stops/smp/sec with an average saturation degree value in each short of 2.02 much higher than the MKJI 1997 provision of 0.85. After changing the phase from 4 phases to 3 phases, the initial green phase still gets a DS value that is not better / better. After the calculation analysis is complete, the next mapping will be carried out at the Meulaboh Range intersection in West Aceh using the Geographic Information System (ArcGIS).